1999
DOI: 10.2466/pms.1999.88.1.292
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Music on Wingate Anaerobic Test Performance

Abstract: While several studies have investigated the effects of music on cardiovascular endurance performance and perceived exertion during exercise of moderate intensity, few studies have investigated such effects on supramaximal exercise bouts. The purpose of the present study was to assess whether music affects performance on the Wingate Anaerobic Test. Each of the 12 men and 3 women were required to report to the laboratory on two occasions, once for tests in the music condition and once for tests in the nonmusic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 8 publications
6
63
4
Order By: Relevance
“…In the study participated 12 males and 3 females. The results showed that the time to exhaustion, fatigue index, the average power output, the maximum and minimum power output in comparison to listening to music, there was no significant differences (Pujol, Langenfeld, 1999). That is inconsistent with results, of course, favorite and light music didn't cause any significant changes in fatigue index, the average power output and maximum power and minimum power had significant change in light music condition.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…In the study participated 12 males and 3 females. The results showed that the time to exhaustion, fatigue index, the average power output, the maximum and minimum power output in comparison to listening to music, there was no significant differences (Pujol, Langenfeld, 1999). That is inconsistent with results, of course, favorite and light music didn't cause any significant changes in fatigue index, the average power output and maximum power and minimum power had significant change in light music condition.…”
Section: Discussioncontrasting
confidence: 45%
“…This result is antithetic with previous findings showed listening to music in an activity that was performed with low intensity was more effective to activities that was performed with maximum intensity (Karageorghis, Drew, Terry, 1996). Pujol and Langenfeld (1999) studied the effect of music on Wingate anaerobic test. In the study participated 12 males and 3 females.…”
Section: Discussionsupporting
confidence: 38%
“…We then analyzed these songs and discovered that they featured either many subdivisions per beat (faster) or very few subdivisions per beat (slower). This phenomenon was made especially clear by the presence of two clips from different parts of the same song 7 . The first clip was consistently perceived as being much faster than the actual tempo, whereas the second clip was considered to be much slower despite featuring the same core tempo.…”
Section: ) Perceived Song Speed Studymentioning
confidence: 99%
“…The cell in bold high- 6 They were different participants from the runners in the running study. 7 Presidents of the United States of America -"Naked and Famous". A few interesting observations can be drawn from the Table: 1.…”
Section: ) Perceived Song Speed Studymentioning
confidence: 99%
See 1 more Smart Citation